ANALISIS PENGARUH KESEHATAN KERJA DAN KESELAMATAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PT MS - Rosdiana rosdiana (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2021)
This study aims to determine the effect of occupational health and safety on employee productivity at PT MS. The research method used is associative research. The data collection technique used is a questionnaire. The instrument of data analysis used chi squared analysis of k samples. The results showed that there was an effect of occupational health and safety on the productivity of PT MS employees.